Leaders as motivators and meaning makers: How perceived leader behaviors and leader safety commitment attributions shape employees’ safety behaviors - Fruhen, L.S.; Andrei, Daniela; Griffin, Mark (2022)
Theory and research identify leadership behaviors as critical for safety outcomes at work. To gain further understanding of the nature of leadership's link with employee safety behaviors, we examine the joint role of generic perceived leadership behaviors (i.e., leader support and inspirational communication) and employee attributions of their leaders’ safety commitment (i.e., affective, normative and calculative safety commitment) in shaping employee safety behavior (i.e. participation and compliance). A sample of workers from the resources industry (N = 1503) responded to survey questions online. Results indicated that employees’ affective leader safety commitment attributions were positively linked to both types of employees’ safety behaviors, while employees’ calculative leader safety commitment attributions were associated only with lower levels of employee compliance. Employees’ normative leader safety commitment attributions were not linked to self-reported employee safety behavior. Moderation analysis indicated that the motivating effects of perceived inspirational leader communication and perceived leader support on safety participation were affected by high levels of normative and affective safety commitment attributions, but not calculative safety commitment. The results illustrate the distinct functions of perceived leadership behaviors and different attributions of leaders’ safety commitment in motivating safety behavior in employees. They suggest reflection about safety commitment and its projections to employees to have add-on value in safety leadership training and development.